1993
DOI: 10.1038/ki.1993.362
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the renal erythropoietin-producing cells using transgenic mice

Abstract: Regulation of erythropoietin production by the kidneys is central to the control of erythropoiesis. Uncertainty about the identity of the renal cells involved has been a major obstacle to understanding this mechanism. We have used sequence from the mouse erythropoietin locus to direct expression of a marker gene, SV40 T antigen, to these cells in transgenic mice. The transgenic constructs contained an oligonucleotide marker (Epo-M) or SV40 sequence (Epo-TAg) in the 5' untranslated region of the mouse erythropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
244
1
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(257 citation statements)
references
References 38 publications
7
244
1
3
Order By: Relevance
“…When hematocrit is in the normal range, the kidney produces a low level of EPO, with EPO expression limited to a small number of these fibroblasts in the deep cortex and superficial outer medulla [2][3][4]. The increased production of EPO under anemic circumstances involves progressive recruitment of additional interstitial fibroblasts in a pattern that spreads outward from the deep cortex toward the capsule and the inner medulla.…”
Section: Mechanisms Of Renal Erythropoietin Productionmentioning
confidence: 99%
“…When hematocrit is in the normal range, the kidney produces a low level of EPO, with EPO expression limited to a small number of these fibroblasts in the deep cortex and superficial outer medulla [2][3][4]. The increased production of EPO under anemic circumstances involves progressive recruitment of additional interstitial fibroblasts in a pattern that spreads outward from the deep cortex toward the capsule and the inner medulla.…”
Section: Mechanisms Of Renal Erythropoietin Productionmentioning
confidence: 99%
“…Intriguing is that individual fibroblasts seem to be recruited in an all-or-none manner (91). At maximal stimulation, it seems that almost all of the fibroblasts of the cortex and the outer medulla activate expression of the EPO (82).…”
Section: Epo Productionmentioning
confidence: 99%
“…One reason for this is no renal fibroblast cell line that expresses the EPO gene has yet been generated. When hematocrit is in the normal range, the kidney produces a low level of EPO, with EPO expression limited to a small number of interstitial fibroblasts in the deep cortex and superficial outer medulla (82,91,92). Anemia results in a dramatic increase in EPO production, resulting in a rise in up to 3 orders of magnitude in the circulating level.…”
Section: Epo Productionmentioning
confidence: 99%
“…This latter observation could suggest the putative existence of another exon located 5' to the published Epo gene structure. Many studies focused on the mechanisms regulating Epo gene expression have shown that the cis-acting sequences involved in hepatic and renal expression of Epo were di erent (Semenza et al, 1990(Semenza et al, , 1991Maxwell et al, 1993); moreover, Epo expression has also been detected in the brain (Masuda et al, 1994;Digicaylioglu et al, 1995). SpeciÂźc expression in di erent tissues could involve alternative promoters of the same gene, as it was described for the porphobilinogen deaminase (Chre tien et al, 1988), pyruvate kinase (Noguchi et al, 1987), (Max-Audit et al, 1993) and choline acetyl transferase genes (Chireux et al, 1995).…”
mentioning
confidence: 99%